A New Indobathynella Species from an Indian Cave. The First Cavernicolous Bathynellidae (Syncarida: Bathynellacea) from South-eastern India - Shaik, Shabuddin (Zootaxa, 2019)
Indobathynella socrates n. sp. is described from Karaiguda Cave in the Visakhapatnam District of Andhra Pradesh state, south-eastern India. This is the first cavernicolous species of Indobathynella, which is incidentally the most reduced genus in the family Bathynellidae as a whole. The type species of this genus, Indobathynella prehensilis, is from a farm bore. The new species fulfils all the principal generic criteria of Indobathynella, but is distinctly different from I. prehensilis in several essential features: absence of subapical seta on antennary exopod; 4 claws on distal maxillulary endite; 6 teeth on mandibular gnathobase, and uropodal exopod without ventro-medial seta. These and all other salient differences between the two species are tabulated. Besides providing brief notes on conservation and biogeography of the new species, a key to all the known Indian taxa of Bathynellidae is given for the first time.